2017
DOI: 10.18203/2320-1770.ijrcog20172047
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in incidence, type, indication and maternal outcome of peripartum hysterectomy over 10 years at a tertiary care centre

Abstract: Background: Peripartum hysterectomy is the most dramatic operation in modern obstetrics and is generally performed when all conservative measures fail to achieve haemostasis in the setting of life threatening haemorrhage. The objective was to review all peripartum hysterectomies performed at a tertiary care centre over a ten-year period from 2007 to 2016 to determine the incidence, types, indications and maternal outcome and also to study the changing trendsMethods: This was a retrospective, observational, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…29 In India, this rate varies between 26% and 88.09%. 11,12,23,30 Total hysterectomy is indicated for placenta accreta, which is the main indication in developed countries. Indeed, subtotal hysterectomy is indicated if the source of the bleeding is upstream of the lower segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In India, this rate varies between 26% and 88.09%. 11,12,23,30 Total hysterectomy is indicated for placenta accreta, which is the main indication in developed countries. Indeed, subtotal hysterectomy is indicated if the source of the bleeding is upstream of the lower segment.…”
Section: Discussionmentioning
confidence: 99%
“…In India, maternal mortality ranges from 2.2% to 16.7%. [9][10][11][12]23,30 Studies in Africa have found a higher frequency. Obiecchina found up to 31% of maternal deaths, Nayama found 21.95% of deaths.…”
Section: Discussionmentioning
confidence: 99%